(1-Butyl-1,4-diaza-bicyclo-[2.2.2]octon-1-ium-N 4) trichloridocobalt(II) - Sanchai Luachan (2018)
The title compound, [Co(C10H21N2)Cl3], was obtained as the by-product of the attempted synthesis of a cobalt sulfate framework using 1,4-diaza-bicyclo-[2.2.2]octane as an organic template. The asymmetric unit comprises two distinct mol-ecules, and in each, the cobalt(II) ions are tetra-hedrally coordinated by three chloride anions and one 1-butyl-diaza-bicyclo-[2.2.2]octan-1-ium cation. The organic ligands are generated in situ, and exhibit two forms differentiated by the eclipsed and staggered conformations of the butyl groups. These mol-ecules inter-act by way of C - H⋯Cl hydrogen bonds, forming a three-dimensional hydrogen-bonding array.